Mnemonics and Their Effect on Students’ Vocabulary Memorization and Recall: A Quantitative Study - Iwan Kurniarahman (BATARA DIDI : English Language Journal, 2023)
Having a Quasi Experimental Research design, this study aimed to reveal the fact whether Mnemonic Keyword is more effective in helping students to memorize and store vocabulary in the short and long term compared to Mnemonic Loci. Twenty-nine students of class IXB (Experimental group) and 31 students of class IXA (Control group) were involved in this study. The Experiment Group was required to memorize vocabulary by using Mnemonic Keyword while the Control group was required to use Mnemonic Loci in memorizing English vocabulary. Right after the last treatment session, the participants were given a post-test to find out the ability of the participants in both groups regarding their ability to store and recall vocabulary in short-term memory. The results revealed that the Experimental group and the Control group had the same performance. Exactly one week after the first post-test, the researcher conducted a second post-test which aimed to find out the ability of the participants in both groups regarding their ability to store and recall vocabulary in long-term memory. The results revealed the fact that the Experimental group had better performance than the Control group in terms of vocabulary retention and recall in long-term memory. This research also revealed the fact that Mnemonic Keyword was more interesting and unique for students during the vocabulary memorization process so that it made them more enthusiastic in memorizing English vocabulary.